Tulul Kobeba: First results of survey and excavation at a looted early medieval ‘marsh Arab’ township in Dhi-Qar province, southern Iraq - Simpson, St John (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2022)
In 2021, a season of survey and excavation was carried out at the site of Tulul Kobeba, near the town of Ar Rifa’i, in Dhi-Qar province, southern Iraq. This was the first time this previously looted site had attracted serious archaeological attention, and the results already offer significant new information on daily life, local industries and the impact of Islam on a small early medieval community in this part of Iraq. Geoarchaeological investigations prove that during the latter period it was a local hub in a region of wetland, but its main function was as an industrial centre for the production of so-called ‘synthetic basalt’ rotary querns made from high-fired clay and chipped into form. A small mosque was found at the centre of the site, surrounded by private residences. Finds on the floors of these houses suggest that it may have been abandoned suddenly and the last period of occupation dates to the 8th century. However, the site was also occupied in the period immediately preceding, and the site offers an important opportunity of obtaining a new sequence showing the development from the late Sasanian to early Islamic periods. Moreover, a ‘magic bowl’ was found in situ near the threshold of one house, the first such archaeological find from this region for many years. There was also intermittent occupation of much earlier periods, including Early Dynastic, Ur III/Isin-Larsa, late Babylonian and possibly Seleucid/Parthian. These periods also produced some significant finds, including an eastern Iranian stone vessel and another carved in low relief.